A Case of Sacroiliitis Developing After Löfgren's Syndrome - Gülcan GÜRER,; Ayşe İYİYAPICI UNUBOL,; Gülnur TAŞÇI BOZBAŞ3, (Archives of Rheumatology, 2011)
Löfgren's syndrome is a form of acute-type sarcoidosis that is characterized by an association with erythema nodosum and bilateral hilar lymphadenopathy accompanied by arthritis or arthralgia. Sacroiliitis has been described in sarcoidosis but is thought to be very rare. In this article, a 38-year-old female with Löfgren's syndrome and sacroiliitis is described, and previously reported cases involving sarcoid sacroiliitis are briefly reviewed.